Laser welded superelastic Cu–Al–Mn shape memory alloy wires. (15th January 2016) - Oliveira, J.P.; Panton, B.; Zeng, Z.; Omori, T.; Zhou, Y.; Miranda, R.M.; Braz Fernandes, F.M.
Abstract: This paper presents the first study on welding of Cu-based shape memory alloys. The superelastic wires used in the investigation had a nominal composition of Cu–17Al–11.4Mn (at.%). The pulsed Nd:YAG spot welding process altered the original bamboo-like microstructure of the base metal to a fusion zone with fine equiaxed grains. Micro-load-indentation depth analysis revealed that the grain refinement increased the ductility of the fusion zone compared to the base material. Tensile tests did not show any significant difference between base material and welded specimens, with failure occurring far away from the welds in the larger grained base metal. Mechanical cycling and superelastic behavior of the welded joints showed a faster stabilization of the hysteretic response than the base material, which is beneficial for applications where energy absorption is required. The Cu–Al–Mn superelastic alloy had a very high weldability and superior properties compared to other laser welded shape memory alloys, such as NiTi. Graphical abstract: Highlights: A first study on welding of Cu-based shape memory alloys is presented. No degradation of tensile properties was observed in the welds. Fracture of the welded tensile samples always occurred in the base material. Welded samples exhibited superelastic behavior.